Pediatric fibromyalgia - J. Ablin; D. Buskila (PAGEPress Publications, 2012)
Fibromyalgia (FM) is currently defined as chronic widespread pain (CWP) with allodynia or hyperalgesia to pressure pain. It is classified as one of the large group of soft-tissue pain syndromes. Pain is the cardinal symptom of FM; however, most patients also experience additional symptoms such as debilitating fatigue, disrupted or non-restorative sleep, functional bowel disturbances, and a variety of neuropsychiatric problems, including cognitive dysfunction, anxiety and depressive symptoms. Its pathogenesis is not entirely understood, although it is currently believed to be the result of a central nervous system (CNS) malfunction that increases pain transmission and perception. FMS usually involves females, and in these patients it often makes its first appearance during menopause. But it is often diagnosed both in young as well as elderly individuals. Pediatric FMS is a frustrating condition affecting children and adolescents at a crucial stage of their physical and emotional development. Pediatric FMS is an important differential diagnosis to be considered in the evaluation of children suffering from widespread musculoskeletal pain, and must be differentiated from a spectrum of inflammatory joint disorders such as juvenile idiopathic arthritis (JIA), juvenile ankylosing spondylitis, etc. The management of pediatric FMS is centered on the issues of education, behavioral and cognitive change (with a strong emphasis on physical exercise), and a relatively minor role for pharmacological treatment with medications such as muscle relaxants, analgesics and tricyclic agents.